(untitled) (Forum Penelitian Agro Ekonomi, 2022)
The Indonesian Agency for Agricultural Research and Development (IAARD) has created various technology packages, significantly superior rice varieties with high yields and resistance to various pests and diseases. Since 1943 hundreds of superior varieties of rice have been released. However, domestic rice production has yet to be able to meet the national rice needs. One of the main problems is the decrease in fertile land due to continuous land conversion. Hence, the mainstay in increasing rice production is to escalate productivity through technological improvements. Therefore, IAARD continues to create new high-yielding rice varieties through plant breeding. More than 200 high-yielding varieties of rice have been produced to meet the challenge of increasing productivity. This paper aims to examine the historical profile of the creation of superior rice varieties in line with intensification programs and their role in increasing national rice production. The study was conducted using a desk study approach by examining secondary data and literature from various publications. The study results showed that creating high-yielding varieties accompanied by various intensification programs had increased rice productivity sustainably. The challenge for IAARD is the creation of new high-yielding varieties with higher yields than those currently available.